Pemodelan Pembangkit Listrik Tenaga Bayu Kecepatan Variabel untuk Analisis Aliran Daya - Rudy Gianto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
The use of variable speed wind turbines (pembangkit listrik tenaga bayu, PLTB) for electricity generation has increased. It contrasts with the fixed-speed PLTB, whose usage is decreasing. The major reason for PLTB’s rapid development is that it has better wind power extraction or collection capabilities than the fixed-speed PLTB. Variable speed operation in a PLTB can be achieved using a doubly-fed induction generator (DFIG) application as the primary energy converter. The crucial initial step in investigating and analyzing power system containing PLTB that must be done is modeling all the components of the power system (including PLTB). An analysis of this power system is mostly conducted to evaluate its performance or appearance. This paper discusses the DFIG-based modeling of the variable speed PLTB to be applied in a power flow analysis of electric power systems. The proposed PLTB model was obtained based on formulas that calculate the power and power losses of the PLTB. The typically challenging power electronics converters modeling of DIFG was not required during the process of building the model. It differs from the previously reported methods in which two different models must be used to accommodate the power flow analysis in subsynchronous or super synchronous conditions. In this paper, the DFIG-based PLTB is represented through a mathematical model. This model could be used to express the DFIG, either in the subsynchronous or super synchronous conditions. It was subsequently integrated into the power flow analysis to evaluate the system’s steady-state performance. The results of this case study will be further presented in this paper. In this study, the application of the proposed methods in the interconnected powers system containing PLTB was then examined. The results confirm the validity of the proposed DFIG model.